Strategic Governance Through Communities and Sustainable Community Empowerment in Prapatan Subdistrict, Balikpapan City - Dipa, Pradeka Reza; Saipul, Saipul; Kus, Indarto (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study examines the implementation of participatory governance and sustainable empowerment in Kelurahan Prapatan, Balikpapan City, emphasizing the institutional role, community participation dynamics, and strategic innovation mechanisms that collectively shape local governance performance. The research explores how institutional leadership, participatory culture, and collaborative partnerships contribute to the creation of adaptive and inclusive governance systems aligned with the principles of good governance and the Sustainable Development Goals (SDGs). The study employs a qualitative descriptive method with a thematic analysis approach to interpret the interrelations among institutional practices, community empowerment processes, and cross-actor coordination. The findings reveal that sustainable empowerment emerges through the integration of institutional strengthening, participatory leadership, community-based transparency, and cross-sector collaboration, forming a cohesive governance ecosystem that enhances accountability, inclusivity, and long-term resilience. The results highlight that effective governance is not solely defined by administrative capacity but by its ability to orchestrate diverse stakeholders toward shared goals of empowerment and sustainability.